Assessment of Anteroposterior Diameter, Interpedicular Distance and Cross-Sectional Area of the Lubar Spine in Patients Undergoing CT Scan in a Tertiary Care Center - Acharya, Sabanam; Pradhan, Sunil; Sharma, Prakash; Bajimaya, Neha (Nepal Journal of Medical Sciences, 2023)
Introduction: Lumbar spinal stenosis is a frequent cause of low back pain. Decreased lumbar spinal canal parameters are major risk factors for canal stenosis. This study was done to assess anteroposterior diameter, interpedicular distance and cross-sectional area of the lumbar spinal canal on a CT scan. Methods: It was a cross-sectional descriptive study conducted at Nepal Medical College Teaching Hospital. Anteroposterior diameter, interpedicular distance and cross-sectional area of the lumbar spinal canal were measured. Results: A total of 171 subjects were selected. The mean of anteroposterior diameter from L1-L5 was 16.46 mm, 16.05 mm, 15.04 mm, 15.08 mm and 15.23 mm respectively. The means of interpedicular distance from L1-L5 were 22.71 mm, 23.20 mm, 24.52 mm, 26.29 mm and 29.90 mm respectively. The means of cross sectional area from L1-L5 were 288.79 mm2, 2773.15 mm2, 266.84 mm2, 282.89 mm2 and 317.04 mm2 respectively. A statistically significant difference between sex and anteroposterior diameter was noted at L2 and the interpedicular distance was at L4 and L5 levels. The cross-sectional area has increased with increased age in all five vertebral levels but it showed statistically significant variation only at L1. Conclusion: Anteroposterior diameter, interpedicular distance and cross-sectional area varies at each level on the lumbar vertebra and may vary according to age and sex.